GAP Ratio, Posisi Devisa Neto, Biaya Operasional Pendapatan Operasional dan Profitabilitas pada Perbankan di Indonesia - Wijayani, Dahyang Ika Leni; Andriasma, Raulita Azizah Brilliant; Ghozali, Saiful (E-Jurnal Akuntansi, 2022)
This research intends to examine the factors that influence the profitability of the banking industry since, as a sector that influences economic circumstances, the banking industry has witnessed fluctuations in profitability over the previous decade. This form of study employs quantitative secondary data sources. The population of this research consisted of all state-owned banks from 2010 to 2021. Multiple linear regression test and also hypothesis testing are employed in this study. Using descriptive quantitative statistics, the technique of analysis explains the relationship between the dependent and independent variables. The study's findings give empirical proof that gap ratio and BOPO have a negative impact on ROA. Meanwhile, PDN has no impact on ROA. This study also demonstrates the validity of the theory of asset-liability management (ALMA); maximizing earnings via risk-managing the structure of the business's financial situation and the anticipated income theory; increasing bank liquidity and optimize bank earnings by offering efficient long-term lending. Keywords: Gap Ratio; Net Open Position (NOP); Operating Cost of Operating Income (BOPO); Profitability (ROA)